Getting Sidetracked: Display Design and Occasioning Photo-Talk with the Photohelix - Hilliges, Otmar; Kirk, David (Proceedings of the 27th International CHI Conference on Human Factors in Computing Systems, 2009)
In this paper we discuss some of our recent research work designing tabletop interfaces for co-located photo sharing. We draw particular attention to a specific feature of an interface design, which we have observed over an extensive number of uses, as facilitating an under-reported but none-the-less intriguing aspect of the photo-sharing experience – namely the process of ‘getting sidetracked’. Through a series of vignettes of interaction during photo-sharing sessions we demonstrate how users of our tabletop photoware system used peripheral presentation of topically incoherent photos to artfully initiate new photo-talk sequences in on-going discourse. From this we draw implications for the design of tabletop photo applications, and for the experiential analysis of such devices.